Pengaruh Gaya Kepemimpinan Transaksional, Gaya Kepemimpinan Transformasional Dan Kepuasan Kerja Terhadap Kinerja Auditor Di Kantor Akuntan Publik (KAP) - Stellina Permatasari Sugiharta; Michell Suharli (Ultima Accounting : Jurnal Ilmu Akuntansi, 2014)
The objective of this research is to examine the effect of transactional leadership, transformational leadership and job satisfaction towards auditor performance. This research was performed as an attempt to acknowledge which factor could increase auditor’s performance. This research is conducted by using survey method to public accountants working at Public Accountant Firms in Jakarta and Tangerang, in 2013 and have one year minimum for job experience, as respondents. Data analysis was conducted by using multiple regressions model. The result of the test showed that transactional leadership, transformational leadership and job satisfaction can significantly affects auditor’s performance silmutaneously. Transactional leadership and job satisfaction have significant effect towards auditor’s performance partially. The next researches are expected to extend the area for survey and to add more of independent variables that could affect auditor’s performance. Keywords: auditor’s performance, job satisfaction, transactional leadership, transformational leadership